Sun of blood and ruin - Lares, Mariely ([Sun of blood and ruin, 2023)
"Rumor has it on the streets of sixteenth-century New Spain, there's a new vigilante in town serving justice. This reimagining of Zorro-featuring a heroic warrior sorceress-weaves Mesoamerican mythology and Mexican history two decades after the Spanish conquest into a swashbuckling historical fantasy debut with magic, intrigue, treachery, and romance. A new legend begins...in sixteenth-century New Spain, witchcraft is punishable by death, Indigenous temples have been destroyed, and tales of mythical creatures that once roamed the land have become whispers in the night. Hidden behind a mask, Pantera uses her magic and legendary swordplay skills to fight the tyranny of Spanish rule. To all who know her, Leonora de las Casas Tlazohtzin never leaves the palace and is promised to the heir of the Spanish throne. The respectable, law-abiding Lady Leonora faints at the sight of blood and would rather be caught dead than meddle in court affairs. No one suspects that Leonora and Pantera are the same person. Leonora's charade is tragically good, and with magic running in her veins, she is nearly invincible. Nearly. Despite her mastery, she is destined to die young in battle, as predicted by a seer. When an ancient prophecy of destruction threatens to come true, Leonora-and therefore Pantera-is forced to decide: surrender the mask or fight to the end. Knowing she is doomed to a short life, she is tempted to take the former option. But the legendary Pantera is destined for more than an early grave, and once she discovers the truth of her origins, not even death will stop her." -- Front jacket flap.